Schizosaccharomyces pombe Spk1 is a tyrosine-phosphorylated protein functionally related to Xenopus mitogen-activated protein kinase. - Gotoh, Y (1993)
Mitogen-activated protein kinase (MAPK) and its direct activator, MAPK kinase (MAPKK), have been suggested to play a pivotal role in a variety of signal transduction pathways in higher eukaryotes. The fission yeast Schizosaccharomyces pombe carries a gene, named spk1, whose product is structurally related to vertebrate MAPK. Here we show that Spk1 is functionally related to Xenopus MAPK. (i) Xenopus MAPK partially complemented a defect in the spk1- mutant. An spk1- diploid strain could not sporulate, but one carrying Xenopus MAPK could. (ii) Both Spk1 and Xenopus MAPK interfered with sporulation if overexpressed in S. pombe cells. (iii) Spk1 underwent tyrosine phosphorylation as does Xenopus MAPK. Tyrosine phosphorylation of Spk1 appeared to be dependent upon mating signals because it occurred in homothallic cells but not in heterothallic cells. Furthermore, this phosphorylation was diminished in a byr1 disruptant strain, suggesting that spk1 lies downstream of byr1, which encodes a MAPKK homolog in S. pombe. Taken together, the MAPKK-MAPK cascade may be evolutionarily conserved in signaling pathways in yeasts and vertebrates.